Using the Receivables Model to Measure the Quality of Accounting Information and its Impact on Increasing Tax Revenue Collection: Applied study in Iraqi General Tax Authority - Ban Abdul-Kadhm Abdulaali; Nuha Aadi Abd Ali; Alyaa Hussein Mohmmed Ali Alesaa (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The research purposes to assess the effectiveness of the receivables model in enhancing the quality of accounting information (QAF), analyze the relationship between this quality and tax revenue proceeds, and provide recommendations for improving the use of the receivables model in institutions to achieve better tax revenue outcomes. Additionally, it highlights the role of high-quality accounting information systems in increasing tax revenues by enhancing the relevance and reliability of accounting data, making it a vital tool for administrative decision-making that aligns with the demands of today's business environment. The study focuses on the General Authority for Taxes of Iraq for the period from 2015 to 2024 to apply the receivables model in measuring the QAF and its impact on boosting tax revenues. The study came to a number of conclusions, the most significant of which was that the two fundamental characteristics that enable various users to use accounting information for decision-making are relevance and reliability, and For the purpose of determining the general structure of the accounting information system in tax institutions and units in order to increase tax revenue collections, it is necessary to determine the type and nature of reports that require preparation to provide, display and communicate information to the entities and parties benefiting from it.